Religious Moderation Picture Book Innovation for Early Childhood: Teaching Tolerance and Respect for Diversity - Purwani, Annisa (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
This study aims to develop innovative media in the form of picture books as a tool to teach religious moderation values such as tolerance and respect for differences to PAUD students in Purwakarta Regency. By using the Research and Development method based on the ADDIE model (Analyze Design Develop Implement Evaluate). this research is designed to produce educational media that is interesting, interactive, and effective. The initial stage of the research involved a needs analysis through interviews and observations with early childhood educators, which revealed the need for media capable of introducing the concepts of tolerance, respect for differences, and national values from an early age. The design and development process resulted in a picture book with vivid illustrations and stories relevant to children's daily lives, making it easy to understand and interesting. This media was tested in several early childhood education institutions in Purwakarta involving teachers and children as research subjects. The evaluation results showed that the picture storybooks improved children's understanding of the values of religious moderation. The results showed an average of the pre-test score of 22.08 then the Post-Test score reached 53.24, with an average increase of 31.16 with the calculation results showing the t value of -44.56, it can be concluded that the use of picture book media is effective in increasing religious moderation in children aged 5-6 years. With these findings, the developed media can serve as a strategic educational media.